Respuesta :

Answer:

- The series converges

Step-by-step explanation:

Given the series:

∑ -4(-1/2)^(n-1) From n = 1 to ∞

Using the ratio test,

Let a_n = -4(-1/2)^(n-1)

a_(n+1) = -4(-1/2)^n

Now,

|a_n/a_(n+1)| = [-4(-1/2)^(n-1)] ÷ [-4(-1/2)^n]

= |(-1/2)^(-1)|

= |-2|

= 2

Suppose the series converges, the

Limit as n approaches infinity of |a_n/a_(n+1)| exist.

Lim(2) as n approaches infinity

= 2

Therefore, the series converges.

The radius of convergence is 2.

..............................................................

It is possible to find the sum of the series.

Using geometric progression formula

S = a/(1-r)

Where a is the first term of the sequence, and r is the common ratio

The series is

-4, 2, 1, 1/2, ...

a = -4

r = a2/a1 = a3/a2 = ...

a2/a1 = -1/2

a3/a2 = 1/2

Since a2/a1 ≠ a3/a2, the common ratio doesnot exist, and so, the sum doesn't neither.